2003
DOI: 10.1016/s1053-8119(03)00170-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the hippocampal system and the prefrontal cortex in learning language-like rules

Abstract: One of the most influential views on the hippocampal function suggests that this brain region is critically involved in relational memory processing, that is, binding converging inputs to mediate the representation of relationships among the constituents of episodes. It has been proposed that this binding is automatic and obligatory during learning and remembering In addition, neuroimaging studies have highlighted the importance of the prefrontal cortex, in learning, memory, and language processing. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
179
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(202 citation statements)
references
References 54 publications
(63 reference statements)
17
179
5
Order By: Relevance
“…High similarity estimates were related to a greater sensitivity to ungrammatical items. This finding is in a good agreement with previous studies reporting a decreasing activity in the left posterior hippocampus with longer exposure to BROCANTO (Opitz and Friederici, 2003). This decrease in activity was argued to represent decrease in importance of relational processing (Opitz & Friederici, 2004;.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…High similarity estimates were related to a greater sensitivity to ungrammatical items. This finding is in a good agreement with previous studies reporting a decreasing activity in the left posterior hippocampus with longer exposure to BROCANTO (Opitz and Friederici, 2003). This decrease in activity was argued to represent decrease in importance of relational processing (Opitz & Friederici, 2004;.…”
Section: Discussionsupporting
confidence: 93%
“…The artificial language BROCANTO (Opitz & Friederici, 2003) was used to generate the stimulus material. In this artificial grammar system with a total vocabulary of 14 words (e.g., "trul" or "rix") from five word categories: nouns (N), verbs (v), determiners (D, d), adjectives (M) and adverbs (m).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that Friederici and colleagues have explored artificial grammars in a series of experiments, with a view to understand language processing (e.g., Friederici et al, 2006;Opitz & Friederici, 2003. For example, Opitz and Friederici (2003) reported that improved performance in an artificial language led to increased activation of the left inferior frontal gyrus (Broca's area) and decreased activation in the left hippocampal area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Opitz and Friederici (2003) reported that improved performance in an artificial language led to increased activation of the left inferior frontal gyrus (Broca's area) and decreased activation in the left hippocampal area. Some caution is needed before extrapolating such conclusions to AGL.…”
Section: Introductionmentioning
confidence: 99%